La « démission parentale », facteur majeur de délinquance : mythe ou réalité ? - Laurence Giovannoni (Sociétés et Jeunesses en Difficulté)
The « parents’ abdication » of their responsibilities, a major factor in delinquency : myth or reality ?     This article questions the importance of « parents’ abdication » of their responsibilities as part of the process leading to minor delinquency. The article takes evidence from two enquiries conducted for Palissy : one on the town’s minor delinquents, and the other on preventative interventions and support actions for parenthood that should be implemented. The first enquiry explored case files on 44 minors from the area that were judged in 2004. The second enquiry explored a statistical study of 156 support actions for parenthood in order to understand what is at stake when accusations of « parental abdication » are made. The article firstly tries to determine what this expression means and determines that it is based on a collectively constructed notion referring to the idea of a « deficient » style of parental education. The study of educative styles used by parents whose children have been judged and the updating of a diverse range of variables at work in the processes leading to minor delinquency show that, for the people studied, these educational styles do not correspond to commonly held representations of « parents’ abdication » of their responsibilities and as such cannot be considered as the only factor leading to delinquency. In conclusion the author suggests distancing the link between « parents’ abdication » of their responsibilities and minor delinquency without downplaying the question of parental responsibility and assumes that a new penal norm whereby parents can be incriminated for the behaviour of their children is being constructed.